2004
DOI: 10.1002/ajmg.a.20218
|View full text |Cite
|
Sign up to set email alerts
|

Social behavior profile in young males with fragile X syndrome: Characteristics and specificity

Abstract: The present study characterizes distinctive and specific features of social behavior impairment, termed social behavior profile (SBP), in young males with fragile X syndrome (FraX). Fourteen males with FraX and autism (FraX+Aut), ages 3-8 years, were compared with either 41 FraX boys without autism (Aut), 7 age-matched males with developmental language delay and autism (DLD+Aut), or with 11 boys with non-selected (for language delay) idiopathic autism (IA), on several standardized instruments assessing social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
159
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 135 publications
(168 citation statements)
references
References 42 publications
9
159
0
Order By: Relevance
“…The basis for this would be that impairments in social and communicative behaviors occur in general at a lower rate in FXS (i.e., their FXS cohort was not divided according to DSM-IV categories) than in idiopathic ASD [19]. However, several other studies have not found clear behavioral differences between individuals with FXS and ASD and those with idiopathic ASD [10,12,20] (as discussed in the next section). Other features supportive of ASD as a distinctive entity in FXS include comorbid conditions, in particular the higher frequency of seizure disorder in individuals with FXS and ASD (i.e., 10–20% higher than in FXS alone) [21,22].…”
Section: Intellectual Disability In Fxs: Diagnosis Of Asd Reflects Sementioning
confidence: 97%
“…The basis for this would be that impairments in social and communicative behaviors occur in general at a lower rate in FXS (i.e., their FXS cohort was not divided according to DSM-IV categories) than in idiopathic ASD [19]. However, several other studies have not found clear behavioral differences between individuals with FXS and ASD and those with idiopathic ASD [10,12,20] (as discussed in the next section). Other features supportive of ASD as a distinctive entity in FXS include comorbid conditions, in particular the higher frequency of seizure disorder in individuals with FXS and ASD (i.e., 10–20% higher than in FXS alone) [21,22].…”
Section: Intellectual Disability In Fxs: Diagnosis Of Asd Reflects Sementioning
confidence: 97%
“…17 Numerous studies indicate that males with FXS and autism have lower IQs or are more developmentally delayed than males with FXS alone. [59][60][61][62] It is unclear which factors (e.g., reduced IQ) lead to apparently autistic behaviors in individuals with both FXS and ASD. As noted above, symptoms of ID and ASD may overlap considerably, often making it difficult to make a diagnosis of ASD in severely cognitively impaired individuals.…”
Section: Epigenetic Syndromes With An Increased Risk Of Asdmentioning
confidence: 99%
“…The ABC is used for many studies, including studies on syndrome phenotypes and pharmacotherapy effects. Outside Japan, many studies use ABC [6][7][8][9][10][11][12][13] . ABC has 58 questionnaire items in total: 15 irritability items, 16 lethargy items, 7 stereotypy items, 16 hyperactivity items, and 4 inappropriate speech items.…”
Section: Methodsmentioning
confidence: 99%